Membangun Moderasi Beragama di Ruang Digital: Strategi Dakwah Berbasis Parodi pada Kanal YouTube Ustaz Ammi Nur Baits - Hapsako, Catur Baro; Hamidah, Lilik; Arif, Moch. Choirul (STAI Ali bin Abi Thalib Surabaya, 2025)
This study aims to analyze the messages of creed (aqidah) and religious moderation in the YouTube content